Targeting Hypoxia Signaling for Perioperative Organ Injury. (January 2018) - Yuan, Xiaoyi; Lee, Jae W.; Bowser, Jessica L.; Neudecker, Viola; Sridhar, Srikanth; Eltzschig, Holger K.
Abstract : Perioperative organ injury has a significant impact on surgical outcomes and presents a leading cause of death in the United States. Recent research has pointed out an important role of hypoxia signaling in the protection from organ injury, including for example myocardial infarction, acute respiratory distress syndrome, acute kidney, or gut injury. Hypoxia induces the stabilization of hypoxia-inducible factors (HIFs), thereby leading to the induction of HIF target genes, which facilitates adaptive responses to low oxygen. In this review, we focus on current therapeutic strategies targeting hypoxia signaling in various organ injury models and emphasize potential clinical approaches to integrate these findings into the care of surgical patients. Conceptually, there are 2 options to target the HIF pathway for organ protection. First, drugs became recently available that promote the stabilization of HIFs, most prominently via inhibition of prolyl hydroxylase. These compounds are currently trialed in patients, for example, for anemia treatment or prevention of ischemia and reperfusion injury. Second, HIF target genes (such as adenosine receptors) could be activated directly. We hope that some of these approaches may lead to novel pharmacologic strategies to prevent or treat organ injury in surgical patients. Abstract : Published ahead of print July 27, 2017.